2005
DOI: 10.1002/cne.20473
|View full text |Cite
|
Sign up to set email alerts
|

Retinotectal transmission in the optic tectum of rainbow trout

Abstract: Retinotectal transmission has not yet been well characterized at the cellular level in the optic tectum. To address this issue, we used a teleost, the rainbow trout, and characterized periventricular neurons as postsynaptic cells expected to receive the retinotectal inputs to the optic tectum. The somata of periventricular neurons are localized in the upper zone of the stratum periventriculare (SPV), whereas the lower zone of the SPV comprises the cell body layer of radial glial cells. Ca2+ imaging identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The gene structures of mammalian, tilapia, and zebrafish NR1 genes are similar; however, they differ in terms of the exon coding for the C-terminal domain by spliced variants. For example, the teleost NR1 genes lack the C2 sequence (Bottai et al 19971998; Harvey-Girard and Dunn 2003; Cox et al, 2005; Kinoshita et al 2005). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene structures of mammalian, tilapia, and zebrafish NR1 genes are similar; however, they differ in terms of the exon coding for the C-terminal domain by spliced variants. For example, the teleost NR1 genes lack the C2 sequence (Bottai et al 19971998; Harvey-Girard and Dunn 2003; Cox et al, 2005; Kinoshita et al 2005). …”
Section: Resultsmentioning
confidence: 99%
“…NMDARs are heteromers comprising two obligate NMDARs and two NR2 (NR2A-D) or NR3 subunits (NR3A-B) (Cull-Candy and Leszkiewicz 2004). Teleost NMDARs have been cloned from knifefish ( Apteronotus leptorpynchus ), rainbow trout ( O. mykiss ), and zebrafish ( Danio rerio ) (Bottai et al 1997; Harvey-Girard and Dunn 2003; Cox et al 2005; Kinoshita et al 2005). However, in anadromous salmon, only sockeye salmon was registered partial NMDA receptor genes sequence in the NCBI database, but the authors has not published English papers.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 4 A, the vast majority of the isolated cells (labeled with nuclei fluorescent dye DAPI) expressed type IV intermediate filament protein nestin, a protein marker for NPCs [53], and type III intermediate filament protein vimentin, a protein marker for mitotically active [54], neural progenitors [55] and radial glia [56]. Further supporting their identity as immature NSCs, we found that the vast majority of these neurosphere-derived cells did not express MAP2, a protein marker for fully differentiated mature neurons (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The NMDAR is a glutamate receptor channel subtype and mediates most of the fast excitatory synaptic transmission in the central nervous system. It plays important roles in memory formation and retrieval in higher vertebrates (Park et al 2013) and in fish (Kinoshita et al 2005;Nam et al 2004;Cox et al 2005;Gómez et al 2006;Tzeng et al 2007;Sison and Gerlai 2011). NMDAR is comprised of two subunits: the essential NR1 subunit and the differentially expressed NR2A-D subunit (Shipton and Paulsen 2013).…”
Section: Endocrinology Studies On Imprinting and Homing Migrationmentioning
confidence: 99%